TINDAK LANJUT PUTUSAN MAHKAMAH KONSTITUSI NOMOR 22/PUU-XV/2017 TERKAIT KEWENANGAN DEWAN PERWAKILAN RAKYAT DALAM PEMBENTUKAN NORMA BARU (Lex Jurnalica, 2019)
AbstractIn 2017, the Constitutional Court (MK) granted part of the material suit related to the difference in age of marriage in Law Number 1 of 1974 concerning Marriage. Mk stated that differences in the age limit of marriage between men and women in the Act cause discrimination. However, the Court stated that it did not decide on the minimum age for marriage. The Court is of the view that determining the minimum age for marriage is the authority of the House of Representatives (DPR) as the legislator. This paper describes the follow-up to the decision of the Constitutional Court Number 22 / PUU-XV / 2017 using the authority of the House of Representatives in the formation of new norms and judicial considerations in the Constitutional Court ruling Number 22/PUU-XV/2017. This research is an empirical normative legal research. Keywords: Legislative body, house of representatives, constitutional court AbstrakDi tahun 2017 lalu, Mahkamah Konstitusi (MK) mengabulkan sebagian dari gugatan uji materi terkait pembedaan usia perkawinan dalam Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan. MK menyatakan perbedaan batas usia perkawinan laki-laki dan perempuan dalam Undang-undang tersebut menimbulkan diskriminasi. Namun MK menyatakan tak memutuskan batas minimal usia perkawinan. MK berpandangan penentuan batas usia minimal perkawinan merupakan kewenangan Dewan Perwakilan Rakyat (DPR) sebagai pembentuk undang-undang.Paper ini menggambarkan mengenai tindak lanjut putusan Mahkamah Konstitusi nomor 22/puu-xv/2017 terkait kewenangan Dewan Perwakilan Rakyat dalam pembentukan norma baru dan pertimbangan hukum Majelis Hakim dalam putusan Mahkamah Konsitusi Nomor 22/PUU-XV/2017. Penelitian ini merupakan penelitian hukum normatif empiris. Kata kunci :Badan legislasi, dewan perwakilan rakyat, mahkamah konstitusi